Pengaruh Kualitas Pelayanan Frontliner Terhadap Kepuasan Nasabah (Studi Kasus: Bank BJB Syariah Purwakarta) - Dina Surya Ramadhani; Imas Widowati; Sutardjo (Jurnal Teknologika, 2025)
This study ains to determine the effect of service quality provided by frontliner on customer satisfaction levels at Bank BJB Syariah Purwakarta. Service quality is an important factor in creating customer satisfaction,especially in the service banking sector. In this study, five dimensions of service quality used include reliability, responsiveness, assurance, empathy, and physical evidence. The research method used is a quantitative method using SmartPls. Primary data were collected by distributing questionnaires to 100 respondents who are active customers of Bank BJB Syariah Purwakarta. Data analysis was carried out using multiple linear regression methods to evaluate the extent to which each service dimension affects customer satisfaction. The results of this study show a value of physical evidence of 0.000, reliability of 0.010, assurance of 0.000, empathy of 0.006, which means that the four dimensions of service quality have a significant effect on customer satisfaction, but the value of responsiveness of 0.607 means it is not significant on customer satisfaction because its value is >0.05.